Implementation of Environmental Policies : 2010 Environment Strategy - Triana, Ernesto Sanchez; Ortolano, Leonard; Ruta, Giovanni; Dezfuli, Ghazal; Kanakia, Rahul (World Bank, Washington, DC, 2017)
The Bank's environmental agenda has evolved gradually since the 1970s. During the 1970s and 1980s, the main focus was on mitigating the potential environmental damage associated with investment projects using environmental impact assessments (EIA). This approach was formalized in the Bank's environmental assessment (EA) requirements, which today consist of a set of individual environmental policies and procedures. Recent evaluations of the Bank's safeguards policy implementation reveal that shortages in environmental safeguards specialists and inadequate skills mix, among other factors, are affecting the quality of safeguards implementation. This report recommends strengthening the environmental safeguards career track to help elevate the profile of safeguards specialists and provide opportunities for career advancement in the course of doing safeguards work. The report also recommends that there be an organizational restructuring to enhance the Bank's capabilities for conducting effective safeguards work. Furthermore, the report recommends developing a comprehensive training program that will enhance the safeguards skill mix and increase the effectiveness of safeguards support at the Bank. This report also recommends adopting a categorization methodology that reduces reliance on procedures requiring subjective judgments. Next, the report recommends the creation of a systematic program for measuring, reporting, and evaluating the effects of safeguards implementation. It also recommends a move towards substantive compliance and environmental sustainability principles for the safeguards framework. This report also recommends disseminating knowledge of policy instruments, besides environment impact assessments, that are able to produce similar or better outcomes than the Bank's safeguard policy requirements. The design and implementation of instruments for environmental policy can be pursued with a more risk-based and differentiated approach, based on country or borrower capacity. In addition to the mitigation of negative impacts, this report recommends institutionalizing the enhancement of positive impacts and client capacity building measures into the safeguards framework.